Investigation of measles IgM-seropositive cases of febrile rash illnesses in the absence of documented measles virus transmission, State of São Paulo, Brazil, 2000-2004 Investigação dos casos de doenças febris exantemáticas com IgM reagente contra o sarampo na ausência de transmissão documentada do vírus do sarampo, Estado de São Paulo, 2000-2004 - Flávia Helena Ciccone; Telma Regina Marques Pinto Carvalhanas; Ana Maria Sardinha Afonso; Brendan Flannery; Eliseu Alves Waldman (Revista da Sociedade Brasileira de Medicina Tropical, 2010)
INTRODUCTION: To review measles IgM-positive cases of febrile rash illnesses in the State of São Paulo, Brazil, over the five-year period following interruption of measles virus transmission. METHODS: We reviewed 463 measles IgM-positive cases of febrile rash illness in the State of São Paulo, from 2000 to 2004. Individuals vaccinated against measles < 56 days prior to specimen collection were considered to be exposed to the vaccine. Serum from the acute and convalescent phases was tested for evidence of measles, rubella, parvovirus B19 and human herpes virus-6 infection. In the absence of seroconversion to measles immunoglobulin-G, measles IgM-positive cases were considered false positives in individuals with evidence of other viral infections. RESULTS: Among the 463 individuals with febrile rash illness who tested positive for measles IgM antibodies during the period, 297 (64%) were classified as exposed to the vaccine. Among the 166 cases that were not exposed to the vaccine, 109 (66%) were considered false positives based on the absence of seroconversion, among which 21 (13%) had evidence of rubella virus infection, 49 (30%) parvovirus B19 and 28 (17%) human herpes virus-6 infection. CONCLUSIONS: Following the interruption of measles virus transmission, thorough investigation of measles IgM-positive cases is required, especially among cases not exposed to the vaccine. Laboratory testing for etiologies of febrile rash illness aids interpretation of these cases. INTRODUÇÃO: Revisar os casos de doenças febris exantemáticas com IgM reagente contra o sarampo, no Estado de São Paulo, Brasil, durante os cinco anos seguidos a interrupção da transmissão do vírus do sarampo. MÉTODOS: Nós revisamos 463 casos de doenças febris exantemáticas com IgM reagente contra o sarampo, no Estado de São Paulo, Brasil, de 2000 a 2004. Indivíduos vacinados contra o sarampo 56 dias antes da coleta de amostra foram considerados expostos à vacina. Soros da fase aguda e de convalescença foram testados para a evidência de infecção de ...